2013
DOI: 10.1039/c3cc41934g
|View full text |Cite
|
Sign up to set email alerts
|

Cu2Se with facile synthesis as a cathode material for rechargeable sodium batteries

Abstract: A Cu2Se electrode on a copper grid substrate has been directly fabricated by a facile post-selenized method and tested as a positive material for sodium ion batteries. Cu2Se exhibits large reversible capacities (about 250 mA h g(-1)), good cyclic stabilities and low polarization. These results indicate that Cu2Se is a promising candidate as a cathode material for sodium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 16 publications
1
77
0
Order By: Relevance
“…In their study, the transition metal compound of NiCo 2 O 4 was found to reversibly decomposed and formed during discharge and charge processes in SIB which is similar to that in LIB. Subsequently, a vast amount of work demonstrated other conversion compounds such as Sb 2 O 4 and Cu 2 Se react with sodium in a similar fashion with lithium [11,12]. However, the electrochemistry of most conversion compounds with sodium was different from that of the same materials with lithium.…”
Section: Introductionmentioning
confidence: 96%
“…In their study, the transition metal compound of NiCo 2 O 4 was found to reversibly decomposed and formed during discharge and charge processes in SIB which is similar to that in LIB. Subsequently, a vast amount of work demonstrated other conversion compounds such as Sb 2 O 4 and Cu 2 Se react with sodium in a similar fashion with lithium [11,12]. However, the electrochemistry of most conversion compounds with sodium was different from that of the same materials with lithium.…”
Section: Introductionmentioning
confidence: 96%
“…tetragonal-, orthorhombic-, and cubic structures) and variable composition (Cu 2-x Se, 0≤x≤1), which offer an incredible wealth of properties for diverse applications such as thermoelectric conversion, lithium-ion battery, photocatalysis, quantum-dot-sensitized solar cells, and photoacoustic imaging. [5][6][7][8][9][10][11][12][13][14] Nano-scale copper selenides exhibit some unusual properties due to the large surface area, high ratio of surface atoms, and quantum confinement effects. An example is the cuprous selenide (Cu 2 Se) nanoparticles, which are easily oxidized into non-stoichiometric Cu 1.8 Se, and become into surprisingly good p-type semiconductor with over 3000 times of enhancements in electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from the viewpoint of the hard and soft acids and bases (HSAB) theory [34], a framework constructed by soft base Se 2À ions seems to be more suitable for the reversible displacement reaction with hard acid Mg 2+ ions because the strong coordination between Mg 2+ and Se 2À should be suppressed. In fact, the reaction mechanism in both Liand Na-ion batteries with Cu 2 Se cathodes was well discussed based on the displacement reactions [35,36]. Here, we report the reversible displacement reaction of b-Cu 2 Se with Mg 2+ in a cathode of Mg batteries.…”
Section: Introductionmentioning
confidence: 84%